2007
DOI: 10.1158/0008-5472.can-06-3696
|View full text |Cite
|
Sign up to set email alerts
|

Novel Estrogen Receptor-α Binding Sites and Estradiol Target Genes Identified by Chromatin Immunoprecipitation Cloning in Breast Cancer

Abstract: Estrogen receptor-A (ERA) and its ligand estradiol play critical roles in breast cancer growth and are important therapeutic targets for this disease. Using chromatin immunoprecipitation (ChIP)-on-chip, ligand-bound ERA was recently found to function as a master transcriptional regulator via binding to many cis-acting sites genome-wide. Here, we used an alternative technology (ChIP cloning) and identified 94 ERA target loci in breast cancer cells. The ERA-binding sites contained both classic estrogen response … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 34 publications
2
81
1
1
Order By: Relevance
“…Moreover, although some of the TDMRs are located in promoter regions, many functionally relevant binding sites for transcription factors probably exist in regions outside of gene promoters, particularly in introns. [21][22][23][24] We found evidence for this in our previous study, where we reported a positive association between increased methylation of the CpG island at the exon 2/intron 3 region and SF-1 expression in endometriotic tissue. 12 Intriguingly, hypermethylation of this exon/ intron region activates SF-1 mRNA expression in endometriotic cells; however, this region is distinct from the 5 0 promoter sequence, hypermethylation of which classically silences gene expression.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, although some of the TDMRs are located in promoter regions, many functionally relevant binding sites for transcription factors probably exist in regions outside of gene promoters, particularly in introns. [21][22][23][24] We found evidence for this in our previous study, where we reported a positive association between increased methylation of the CpG island at the exon 2/intron 3 region and SF-1 expression in endometriotic tissue. 12 Intriguingly, hypermethylation of this exon/ intron region activates SF-1 mRNA expression in endometriotic cells; however, this region is distinct from the 5 0 promoter sequence, hypermethylation of which classically silences gene expression.…”
Section: Discussionmentioning
confidence: 54%
“…Specifically, ERRLR01 is highly expressed in triple-negative breast cancers, yet not in samples derived from patients with ERα+ tumors. Follow up experiments indicated 17β-estradiol also altered the levels of ERRLR01 in ERα+ cells lines (i.e., MCF-7 and T47D) [25,153] . Given 17β-estradiol is a crucial regulator of EMT [28] , we surmise ERRLR01 and other lncRNAs are crucial mediators of the metastatic cascade.…”
Section: Estrogen Receptor Regulated Lincrna 01mentioning
confidence: 96%
“…Recently, several hundreds of potential transcriptional coregulators that interact directly and indirectly with nuclear receptors have been identified (O'Malley, Qin et al, 2008;Kato and Fujiki, 2011), including fat-soluble ligands like vitamin A/D, steroid hormone receptors, and peroxisome proliferator-activated receptor gamma (PPARγ), which plays critical roles in metabolism and adipogenesis (Kato and Fujiki, 2011;Sugii and Evans, 2011). Genes that represent specific targets of estrogen receptor alpha have been identified using the chromatin immunoprecipitation approach (Jin et al, 2004;Lin et al, 2007), allowing insight into the downstream effectors of hormonal signaling.…”
Section: Insulin-like Growth Factor Receptors Igf1r/igf2rmentioning
confidence: 99%